Improvement of VO2 max in Patient with Restrictive Pulmonary Disorder after Deep Breathing Exercise - Lisa Nurhasanah; Erna Setiawati; Rahmi Isma AP (Indonesian Journal of Physical Medicine & Rehabilitation, 2018)
Introduction: Restrictive pulmonary disorder is reducing VO2 max values. It can be caused by lung can’t take oxygen from outside air freely. Pulmonary rehabilitation is known to increase the VO2 max. One of the pulmonary rehabilitation is deep breathing exercise. In this study aimed to know the improvementVO2 max after deep breathing exercise.Methods: This was an experimental without control pre and post-experimental study. The Six Minutes Walking Test (6MWT) was measured in patients with restrictive pulmonary disorder, after deep breathing exercise two times a day, for four weeks in May 2018.Results: Fifteen subjects were recruited, with the mean age was 70,76 ± 5,33 years old, 6MWT was 375,13 ± 44,19 m and VO2 Max 31,61±0,86 ml/kg/minute. After four weeks intervention, 6MWT value was 401±44,57 m (p=0.000) and VO2 Max score was 32,11±0,87 ml/kg/minute (p=0.000).Conclusion: Four weeks of deep breathing exercise can improve the VO2 max in restrictive lung disorder.Keywords: Deep breathing exercise, Restrictive pulmonary disorder, VO2 max.